Unpacking the geography of tourism innovation in Western Cape Province, South Africa - Booyens Irma; Rogerson Christian M. (Bulletin of Geography. Socio-Economic Series)
This paper interrogates the geography of tourism innovation in the Western Cape, South Africa. In particular, innovations by tourism firms are mapped and local tourism innovation networks are analysed. Networking behaviour is examined since it is regarded as indispensable for accessing knowledge and learning for innovation purposes. The analysis draws on a broader investigation of tourism innovation and networking within the Western Cape province. It is revealed that the main tourist regions in the Western Cape are also the most innovative. Whilst external networking relations are observed to be highly significant for tourism innovation, local embeddedness remains critical for stimulating path creation and exploiting local core competencies for the competitiveness and survival of tourism firms and destinations.